Faithful atheists: the paradox of Jewish nonbelievers in Israel - Friedman, Tammar (Religion, 2025)
This article examines narratives of coping strategies and worldviews adopted by Jewish Israeli atheists (JIA) during times of emotional turmoil. Through qualitative interviews with 30 participants, we demonstrate how they navigate between rational disbelief in God, Jewish identity, and their need for comfort. While valuing rational thinking, they find it insufficient for emotional solace. To cope, they create alternative ‘just-world’ cosmologies, use coded prayers, and draw on Jewish rituals, both revisiting and personalizing them. While the study of atheism often poses a binary logic that pits religious believers against atheists, religion against science and belief against doubt, our study reveals that for JIA these boundaries are far blurrier. Thus, this study contributes to the growing body of literature on lived atheism, highlighting the nuanced and often contradictory ways in which atheists engage with religious and spiritual concepts.